Developing a data sharing framework: a case study. Issue 1 (11th March 2014) - Higgins, Emma; Taylor, Mark; Lisboa, Paulo; Arshad, Farath
Abstract : Purpose: – The purpose of the research project was to examine the process of developing a data sharing framework between different public sector organisations. Design/methodology/approach: – A two-year case study of a data sharing project between a UK fire and rescue service, local council, NHS primary care trust and a police force was undertaken. Findings: – It is important to carefully determine the requirements for data sharing, to establish data sharing agreements, to have secure arrangements for data sharing, and to ensure compliance with data protection legislation. Research limitations/implications: – Data sharing between public sector organisations can operate effectively if appropriate care is taken when creating data sharing agreements between partner organisations. Practical implications: – Data sharing can assist in reducing duplication of effort between public sector organisations and can reduce costs and enable more co-ordinated provision of public services. Originality/value: – The detailed analysis of a data sharing case study identified the need for a systematic data sharing framework. Such a framework is proposed and illustrated with practical examples of specification, implementation and evaluation.